Perbandingan Efisiensi Analisis Teknikal, SMA dan EMA dalam Mengestimasi Harga Saham - Abid Shabrina; Sri Hasnawati (Goodwood Publishing, 2022)
The development of the times also encourages economic growth in every country. With more income, people have a desire to invest their excess income for investment activities. The investment made aims to get a profit or return. Stock return is the result (profit or loss) obtained from a stock investment. This of course requires technical analysis of which there are Simple Moving Average, and Exponential Moving Average. This study aims to compare the two analyzes and which one is more efficient in manufacturing companies on the IDX in 2021. Based on the results of the study, it is known that the Exponential Moving Average with a period of 30 days is an efficient stock price estimation analysis in estimating stock prices from the 4 sub-sectors contained in the mining sector on the Indonesia Stock Exchange in 2021. The Simple Moving Average becomes an analysis of stock price estimates that are less efficient in estimating the share price of the mining sector on the Indonesia Stock Exchange in 2021. The study also found that in the EMA method, the longer the analysis period used, the the better the prediction results with the smaller the variance description value indicator.